Endovascular retrieval of difficult to remove port-a-caths - Raghavendra Rao; Francis E. Marshalleck; Alan P. Ladd (Elsevier, 2019)
Long dwelling central venous lines develop intravenous adhesions or a calcified fibrous sheath causing difficulties in removal. Although such cases are rare, a few cases of endovascular retrieval have been reported in pediatric literature. We report our experience with 6 cases in children with port-a-caths. Transfemoral snare technique was effective in all but 1 patient. The mean age of the in dwelling port-a-caths was 5 years. One patient whose catheter could not be removed has developed no complications after a follow-up of 5 years. Review of literature suggests that while endovascular retrieval is not without risks, leaving a central line in situ has no major disadvantages. Heroic measures to remove such lines should be pursued only when absolutely necessary as in the case of an infected line.